Effect of the Addition of Potassium or Lithium on the Columbite Precursor Microstructure - Cavalheiro, Alberto A.; Zaghete, Maria A.; Paiva-santos, Carlos O. [UNESP]; Varela, José A. (ABM, ABC, ABPol, 2002)
Pechini method has been used to synthesize MN powders with stoichiometric control. By this method, K and Li-doped MN in the range from 0.1 to 5.0 mol% of dopants have been obtained at relatively lower temperatures than it is possible with the conventional mixture of oxides. The results from BET analysis indicated that the doped powders have lower surface area and the attrition milling promotes an increase in surface area values for all powders. Rietveld method was used to calculate the mean crystallite size and the microstrain in the crystal. With additions of up to 5.0 mol% of K or 2.0 mol% of Li, it is possible to obtain MN as a solid solution. Both dopants change the cell parameters of the columbite phase crystal, reduce the microstrain, and increase the main crystallite size. The analysis of results from SEM indicates that powders prepared with addition of dopants are more agglomerate than pure PMN powder.
Keywords: ceramic; columbite; PMN; Pechini and Rietveld method